NERACA PERDAGANGAN KOMODITI KARET ANTARA INDONESIA DENGAN AMERIKA SERIKAT - Widayanti, Sri (MAPETA, 2008)
The aim of this research are 1) to know growth balance of trade rubber commodity between Indonesia and United States. 2)Analysing factors having an effect to balance of trade rubber commodity between Indonesia and United States. Knowing effort to increase balance of trade rubber commodity between Indonesian with United States. This Research using secondery data, of time series from 1992 to 2005. Of the obtained data is hereinafter analysed by using analysis of trend, analyse multiple linear regression and descriptive analysis. Result of research indicate that growth balance of trade rubber commodity between Indonesia and United States from 1992 to 2005 would degradation. By simultan is fourth the variable have an effect on reality to balance of trade rubber commodity between Indonesia and United States. While by partial variable of produce domestic natural rubber, rupiah exchange rate to dollar and interest rate have an effect on positive and signifikan to balance of trade rubber commodity between Indonesian with United States, domestic polystyrene consumption have an effect on negative and signifikan to balance of trade rubber commodity between Indonesian with United States. Effort to increase balance of trade rubber commodity between Indonesian with United States for example: Increase pro duel natural rubber by using pre-eminent clone, taking care of stability of rupiah exchange rate to dollar and need the existence of policy the government that is make-up of lease and add national saving will improve interest rate. Keywords: balance of trade, rubber, Indonesia and United States